In ricordo di Enrico Vitelli - Carlucci, Renzo; Ferrante, Flavio (GEOmedia, 2010)
Remembering Enrico Vitelli Enrico Vitelli has been one of the most important charachters in the Italian geomatics sector. This article celebrates the achievements and the results of his carreer. A carreer and a life devoted to all fields of geomatics. As editor-in-chief of the 'Rivista del Catasto' (Cadastral Magazine) he always gave space to authors and themes that differed from the traditional aspects of topographic, photogrammetric and cadastral issues, promoting a new scientifical vision for the entire sector.